2023
DOI: 10.7759/cureus.39812
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Deoxyribonucleic Acid (mtDNA), Maternal Inheritance, and Their Role in the Development of Cancers: A Scoping Review

Sabitha Vadakedath,
Venkataramana Kandi,
Jayashankar CA
et al.

Abstract: Mitochondrial DNA (mtDNA) is a small, circular, double-stranded DNA inherited from the mother during fertilization. Evolutionary evidence supported by the endosymbiotic theory identifies mitochondria as an organelle that could have descended from prokaryotes. This may be the reason for the independent function and inheritance pattern shown by mtDNA. The unstable nature of mtDNA due to the lack of protective histones, and effective repair systems make it more vulnerable to mutations. The mtDNA and its mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, due to the complex interplay between the mitochondrial and nuclear genomes, it is often difficult to predict disease outcomes based solely on mitochondrial genetic mutations. 68 Genetic predisposition explains less than 10% of cases, so genetic abnormalities alone are unlikely to directly cause the disease. 61,66,[69][70][71][72][73] Despite recent advances in the molecular biology, no PCOS susceptibility genes or candidate genes have been identified to explain the inheritance pattern.…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the complex interplay between the mitochondrial and nuclear genomes, it is often difficult to predict disease outcomes based solely on mitochondrial genetic mutations. 68 Genetic predisposition explains less than 10% of cases, so genetic abnormalities alone are unlikely to directly cause the disease. 61,66,[69][70][71][72][73] Despite recent advances in the molecular biology, no PCOS susceptibility genes or candidate genes have been identified to explain the inheritance pattern.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…mtDNA First, the mammalian mtDNA encodes 2 ribosomal RNAs, 12S rRNA and 16S rRNA, and 13 oxidative phosphorylated subunit proteins. 3,66,68,96 These proteins facilitate the synthesis of ATP by ATP synthase in the…”
Section: Changes In the Glycolysis-related Gene Expressionmentioning
confidence: 99%
“…It is important to remark that the mitochondrial genome displays peculiar features, such as the absence of protective histones that account for a different spatial organization with respect to nuclear DNA [49,50].…”
Section: Bioactive Compounds Influencing Epigenetics At Mitochondria ...mentioning
confidence: 99%
“…In a study conducted by Judit et al [ 61 , 62 ], exoDNA was extracted from blood and plasma samples of 24 patients with serous epithelial ovarian cancers and 24 healthy control subjects. The researchers utilized real-time quantitative PCR to measure the copy numbers of mtDNA.…”
Section: Research Progress On the Application Of Exodna In Lbmentioning
confidence: 99%
“…The increased levels of both free-cell and exosomal mtDNA in advanced cancer align with the characteristics of tumor-derived DNA promoting metastasis [ 65 ]. It can be concluded that an altered mtDNA copy number might serve as a signal for cancer progression in ovarian cancer [ 62 , 63 , 64 ]. Further research will be needed to validate these findings and explore the clinical utility of mtDNA copy number as a biomarker in ovarian cancer patients [ 66 ].…”
Section: Research Progress On the Application Of Exodna In Lbmentioning
confidence: 99%